Successful treatment of chronic venous in-stent restenosis using a Phoenix atherectomy device - Linden, Fabian; Mihu, Thomas; Frey, Norbert; Erbel, Christian (International angiology, 2024)
Although endovascular treatment of venous obstruction with percutaneous transluminal angioplasty (PTA) and stenting is a safe and effective alternative to conservative treatment, the overall prevalence of in-stent restenosis (ISR) remains high in this patient population. This study reports a novel treatment option for patients with chronic ISR (C-ISR).
Gesehen am 13.02.2025